Patterns and underlying mechanisms of non-volant small mammal richness along two contrasting mountain slopes in southwestern China. Issue 1 (December 2017) - Chen, Zhongzheng; He, Kai; Cheng, Feng; Khanal, Laxman; Jiang, Xuelong
Abstract The species richness patterns of small mammals and the processes shaping them in two gradients of a mountain with different spatial and climatic characteristics were examined using standard sampling scheme. We trapped 2, 006 small mammals representing 37 species, along elevational gradients on both western and eastern slopes of the Ailao Mountains, Southwest China. Using mid-domain effect model, model selection and model averaging, we examined the effects of slope, area, mean annual temperature (MAT), mean annual humidity (MAH), productivity, plant species richness (PSR) and the mid-domain effect (MDE) on the patterns of small mammal diversity. The hump-shaped patterns were favored along the elevational gradient, but shapes of diversity curves were different on the contrasting slopes. Area and productivity were the most important factors in explaining the variation of total species richness. However, for each specific group of small mammals (i.e. insectivores vs. rodents, large-ranged vs. small-ranged species, endemic vs. non-endemic species), the peaks of species richness and their primary drivers varied. The major explanatory factors for richness pattern of each small mammal group were not significantly different between the slopes, suggesting the existence of the general underlying mechanisms on two slopes of a mountain.